THE FEDORIVKA LAYERED INTRUSION (KOROSTEN PLUTON, UKRAINE): AN EXAMPLE OF HIGHLY DIFFERENTIATED FERROBASALTIC EVOLUTION - Duchesne J.C.; Charlier B.; Shumlyanskyy L. (My University, 2006)
This study documents the petrography and whole-rock major and trace element geochemistry of 38 samples mainly from a drill core through the entire Fedorivka layered intrusion (Korosten Pluton), as well as mineral compositions (microprobe analyses and separated mineral fraction analyses of plagioclase, ilmenite, magnetite and apatite) of 10 samples. The Fedorivka layered intrusion can be divided into 4 lithostratigraphic units: a Lower Zone (LZ, 72 m thick), a Main Zone (MZ, 160 m thick), and an Upper Border Zone, itself subdivided into 2 sub-zones (UBZ2, 40 m thick; UBZ1, 50 m thick). Igneous lamination defines the cumulate texture, but primary cumulus minerals have been affected by trapped liquid crystallization and subsolidus recrystallization. The dominant cumulus assemblage in MZ and UBZ2 is andesine (An39-42), iron-rich olivine (Fo32-42), augite (En29-35Fs24-29Wo42-44), ilmenite (Hem1-6), Ti-magnetite (Usp52-78), and apatite. The data reveal a continuous evolution from the floor of the intrusion (LZ) to the top of MZ, due to fractional crystallization, and an inverse evolution in UBZ, resulting from crystallization downwards from the roof. The whole-rock Fe/Mg ratio and incompatible element contents (e.g. Rb, Nb, Zr, REE) increase in the fractionating magma, whereas compatible elements (e.g. V, Cr) steadily decrease. The intercumulus melt remained trapped in the UBZ cumulates due to rapid cooling and lack of compaction, and cumulus mineral compositions re-equilibrated (e.g. olivine, Fe-Ti oxides). In LZ, the intercumulus melt was able to partially or totally escape. The major element composition of the MZ cumulates can be approximated by a mixing (linear) relationship between a plagioclase pole and a mafic pole, the latter being made up of all mafic minerals in (nearly) constant relative proportions. By analogy with the ferrobasaltic/jotunitic liquid line of descent, defined in Rogaland, S. Norway, and its conjugated cumulates occurring in the Transition Zone of the Bjerkreim-Sokndal intrusion (Rogaland, a monzonitic (57% SiO2) melt is inferred to be in equilibrium with the MZ cumulates. The conjugated cumulate composition falls (within error) on the locus of cotectic compositions fixed by the 2-pole linear relationship. Ulvöspinel is the only Ti phase in some magnetites that have been protected from oxidation. QUIlF equilibria in these samples show that magnetite and olivine in MZ have retained their liquidus compositions during subsolidus cooling. This permits calculation of liquidus fO2 conditions, which vary during fractionation from ΔFMQ = 0.7 to - 1.4 log units. Low fO2 values are also evidenced by the late appearance of cumulus magnetite (Fo42) and the high V3+-content of the melt, reflected in the high V-content of the first liquidus magnetite (up to 1.85% V). © 2006 Elsevier B.V. All rights reserved.
Keywords: ANORTHOSITE; FE-TI OXIDE MINERALS; FERROBASALT; JOTUNITE; LAYERED INTRUSIONS; VANADIUM